Efficacy of immune check-point inhibitors (ICPi) in large cell neuroendocrine tumors of lung (LCNEC). (May 2020) - Sherman, Shira; Rotem, Ofer; Shochat, Tzippy; Zer, Alona; Moore, Assaf; Dudnik, Elizabeth
Highlights: Our series is one of the first and the largest assessing ICPi efficacy in LCNET. In LCNET, ICPi outcomes are comparable to outcomes observed in NSCLC. In LCNET, ORR with ICPi - 33 %, mPFS with ICPi - 4.2 months. mOS with ICPi: 11.8 and 6.9 months in LCNET and NSCLC, respectively (p-0.23). The correlation with LCNET molecular subtype needs further exploration. Abstract: Objectives: Little is known regarding the ICPi efficacy in LCNEC. We explored the efficacy and safety of ICPi in LCNEC and assessed its impact on OS. Materials and methods: Thirty-seven consecutive patients with advanced LCNEC were selected from the Davidoff Cancer Center database. These were divided into groups A1 (patients treated with ICPi, n-23) and A2 (patients not treated with ICPi, n-14). Additionally, group A1* was introduced (patients treated with ICPi as a monotherapy, n-21). Another cohort of advanced non-LCNEC lung cancer patients treated with nivolumab at five Israeli cancer centers was chosen as a comparator (group B, n-270). ORR, PFS with ICPi in group A1* were assessed (RECIST 1.1), OS with ICPi was compared between groups A1* and B. OS since advanced disease diagnosis (OSDx) was compared between groups A1 and A2. Results: In group A1*, ORR and median PFS with ICPi were 33 %, and 4.2 months (95 % CI, 2.4–8.1), respectively. With median follow-up since start of ICPi of 6.2 months [IQR 2.2–12.1] and 4.9 months [IQR 2.3–8.9] in groups A1* and B, respectively, 52 % and 64 % of patients died in groups A1* and B, respectively. Median OS with ICPi comprised 11.8 months (95 % CI, 3.7-NR) and 6.9 months (95 % CI, 5.5–8.1) in groups A1* and B, respectively (p-0.23). Median OSDx was 14.5 months (95 % CI, 10.1–38.9) and 10.3 months (95 % CI, 2.6-NR), in groups A1 and A2, respectively (p-0.54). Conclusion: In advanced LCNEC, ICPi outcomes are comparable to the outcomes observed in advanced NSCLC. Future research is needed to clarify the impact of ICPi on OS, and to correlate its benefit with tumor mutational landscape.